1982
DOI: 10.1016/0004-6981(82)90049-x
|View full text |Cite
|
Sign up to set email alerts
|

Technique for determining pollutant emissions from a gas-fired range

Abstract: This isa Librart Cifculatinq Copy • whIh m..atj be borrowed for two weeks. • For q personal tctit ion copy, call \ Tech. Info.lvzlsl Ext.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 12 publications
5
61
1
Order By: Relevance
“…Because housing characteristics and ambient concentrations of all pollutants were different between the valley and mountain sites, it was difficult to see a clear relationship between indoor HONO and cooking on a gas range. Under controlled conditions, Traynor et al (27) showed that gas ranges emit HONO at about 11% the rate of NO 2 emissions. Variations in other variables across the homes studied here and the fact that cooking times were not recorded prevented us from examining the direct impacts from cooking on a gas range.…”
Section: Discussionmentioning
confidence: 99%
“…Because housing characteristics and ambient concentrations of all pollutants were different between the valley and mountain sites, it was difficult to see a clear relationship between indoor HONO and cooking on a gas range. Under controlled conditions, Traynor et al (27) showed that gas ranges emit HONO at about 11% the rate of NO 2 emissions. Variations in other variables across the homes studied here and the fact that cooking times were not recorded prevented us from examining the direct impacts from cooking on a gas range.…”
Section: Discussionmentioning
confidence: 99%
“…This is in strong contrast to the characterization of emissions from combustion appliances (Johnson et al, 1984;Leaderer, 1982;Traynor et a/., 1982) and building materials (Girman et al, 1984;Molhave, 1982), where numerous chamber studies have been conducted. In this paper, considerations necessary for evaluating emissions from consumer products in laboratory studies are presented.…”
Section: Introductionmentioning
confidence: 90%
“…The protocol was modified to reflect this change. (Traynor, Anthon and Hollowell, 1982). Because of the temporal variation of emissions from some consumer products, it may be necessary to use a version of this model that can address these variations (Traynor et al, 1985).…”
Section: Task Six: Pretestmentioning
confidence: 99%
“…technique [ 10]. Another technique, often called the "hood" technique, can be used for calculating CO and N0 2 emission rates from unvented gas cooking ranges or other sources that do not significantly reduce the house oxygen levels [ 31 ,32].…”
Section: Pollutant Emission Rates Source Strengths and Venting Factorsmentioning
confidence: 99%